Concave porous silicon carbon particle with high ionic conductivity and preparation method thereof
By designing concave porous silicon carbon particles, the orderly structure of nano -carbon material improves the conductive capacity and absorb silicon expansion stress, solving the problem of cracking and conductive channels caused by expansion stress in lithium ion batteries in lithium ion batteries. Realize higher cycle life and work stability.
Patent Information
- Application Number
- CN202411500116.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-25
AI Technical Summary
During the long-term cycle charging and discharging process of lithium-ion batteries, traditional silicon-carbon composite materials cause particle cracking, negative electrode film cracking and conductive paths to deteriorate due to the volume expansion of silicon, resulting in negative electrode capacity attenuation and poor working stability.
Design a concave porous silicon carbon particle with high ion conductivity, and its surface is provided with partial surface depressions to form a cross-linked body of silicon debris and carbon nanomaterials with continuous and arc-shaped boundaries. The particles are prepared by spray drying and high-temperature sintering. The nanocarbon material forms an ordered structure, improves electrical conductivity and acts as a buffer structure to absorb silicon expansion stress.
It improves the internal conductivity and ion transmission capabilities of silicon-carbon particles, avoids cracking and falling off of silicon-carbon particles and negative electrodes, extends the cycle life of lithium-ion battery negative electrodes and improves working stability.
Smart Images

Figure CN119361645A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon composite materials, in particular to concave porous silicon-carbon particles with high ion conductivity and a preparation method thereof. Background Art
[0002] The specific capacity of a lithium-ion battery is determined by both the positive and negative electrode specific capacities, with the higher the negative electrode specific capacity, the better. Traditional graphite negative electrode products have a specific capacity of around 350-370 mAh / g, essentially reaching their theoretical limit. Silicon, however, boasts a theoretical specific capacity of up to 4200 mAh / g, offering significant advantages.
[0003] Silicon undergoes a 300% volume expansion during the charge and discharge process. Silicon and porous amorphous carbon composites are typically used to buffer the stress generated by this expansion. However, porous amorphous carbon has relatively weak strength and toughness. After long periods of cyclic charge and discharge, frequent scaling can cause the bonding and interface fractures between the silicon-carbon composite particles, leading to particle collapse and cracking of the negative electrode film, significantly attenuating the negative electrode. In silicon-carbon research, many techniques involve mixing nanoscale and submicron silicon particles with carbon to form secondary particles, or forming a carbon coating on the surface of silicon particles before forming secondary particles. With such materials, during long-term cycling, the alloying of silicon causes expansion and extrusion between the secondary particles. The collapse during dealloying causes depressions on the secondary particle surface and increases the gaps between the secondary particles in the negative electrode, deteriorating the negative electrode's conductive path. In addition, expansion and extrusion will also cause the secondary particles to crack, forming a new solid-liquid interface. A large amount of irreversible amorphous lithium / silicon / oxygen compounds will be produced on the surface of the secondary particles in the negative electrode. The gaps and the above products will not only hinder the transmission of ions in the negative electrode, but also cause the negative electrode layer to pulverize and fall off. Therefore, the overall capacity of the silicon-carbon negative electrode is prone to rapid attenuation and poor working stability. Summary of the Invention
[0004] In order to overcome the deficiencies of the prior art, the present invention provides concave porous silicon-carbon particles with high ion conductivity and a preparation method thereof.
[0005] To achieve the above purpose, a concave porous silicon-carbon particle with high ion conductivity is designed. The surface of the concave porous silicon-carbon particle is partially depressed to form a cross-linked body of silicon debris and carbon nanomaterials with continuous and arc-shaped boundaries.
[0006] To achieve the above objectives, a method for preparing concave porous silicon-carbon particles with high ionic conductivity is designed, comprising the following steps: S1, mixing a modifier, a surface modification solvent and silicon powder, stirring, and drying to obtain surface-modified silicon powder; S2, adding the surface-modified silicon powder, water-soluble carbon source, soluble inorganic salt and carboxylated carbon nanomaterial into the acidic aqueous solution and mixing them uniformly; S3, the mixed solution is passed through a spray dryer to prepare micron-sized silicon-carbon secondary particles, which are then sintered at high temperature in a vacuum furnace under the protection of an inert gas and cooled to room temperature; S4: After high-temperature sintering, the product is washed to remove soluble inorganic salts and then dried at low temperature under vacuum to obtain the final product.
[0007] In step S1, the modifier is selected from one of organosiloxane, polyether-modified hydrophilic water-soluble silicone oil, and PVP hydrophilic solvent. The modifier mainly changes the hydrophilic properties of the silicon surface, thereby increasing its hydrophilicity.
[0008] The surface modification solvent is selected from one of silane coupling agent, titanate, and stearic acid; the silane coupling agent includes but is not limited to one of amino, epoxy, and vinyl.
[0009] In the step S1, the silicon powder is selected from crystalline silicon particles of arbitrary shape, with a size of 100-500 nm, and a dimension of the particles in one direction is less than 200 nm; the mass ratio of the modifier to the silicon powder is 2.5-8:16, so that the thickness of the molecular layer covering the surface of the silicon particles is 3-20 nm.
[0010] In step S2, the water-soluble carbon source is an aqueous solution of a polar polymer, including but not limited to an aqueous polyurethane resin solution, a water-soluble polyethylene glycol solution, and a methyl cellulose solution; the carboxylated carbon nanomaterial is one or more of carboxylated carbon nanotubes, carboxylated graphene, and carboxylated carbon nanofibers; and the radial dimensions of the carboxylated carbon nanomaterial in different directions are less than 300 nm.
[0011] In step S2, the soluble inorganic salt is selected from one or more inorganic salts that can crystallize at 80-100°C and dissolve in water, including but not limited to one or more inorganic salts such as potassium salt, sodium salt, ammonium salt, nitrate, acetate, etc. that can crystallize at 100°C and dissolve in water.
[0012] In step S2, the acidic aqueous solution includes at least one of weakly acidic acetic acid solution, citric acid solution, acetic acid solution, and carbonic acid, and the pH value is 3-5.
[0013] In step S2, the mass ratio of silicon to carbon element in the water-soluble carbon source is 1:1 to 3, the mass ratio of the soluble inorganic salt to silicon is 1:1 to 1.5, and the mass ratio of silicon to carboxylated carbon nanomaterial is 1:0.1 to 0.5.
[0014] In step S3, the inert gas is selected from nitrogen and argon, the sintering temperature is 800-900° C., and the holding time is 0.5-1.5 hours.
[0015] Compared with the prior art, the nano-carbon material in the particles of the present invention has an ordered structure, which improves the internal conductivity and ion transmission capacity of the silicon-carbon particles. At the same time, it can also serve as a buffer structure to absorb silicon expansion stress, avoid cracking of the silicon-carbon particles, and also avoid cracking and falling off of the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the SEM image of the concave porous silicon-carbon particles SCT with added carbon nanotubes of the present invention.
[0017] Figure 2 A comparison chart of the pore size test results of particles without carbon nanotubes (SC) and particles with carbon nanotubes (SCT).
[0018] Figure 3 This is the SEM image of concave porous silicon-carbon particles SCG with added carbon nanotubes.
[0019] Figure 4 These are SEM images of the electrode without carbon nanotubes (a) and the electrode with carbon nanotubes (b) after charge and discharge cycles.
[0020] Figure 5 The failure mechanism simulation diagram of particles without carbon nanotubes (SC) and particle negative electrodes with carbon nanotubes (SCT) during the cycle process. DETAILED DESCRIPTION
[0021] The present invention will be further described below with reference to the accompanying drawings.
[0022] like Figure 1 As shown, the surface of the concave porous silicon-carbon particles is partially depressed, forming a cross-linked body of silicon debris and carbon nanomaterials with continuous and arc-shaped boundaries.
[0023] The method for preparing the concave porous silicon-carbon particles with high ionic conductivity comprises the following steps: S1, mixing a modifier, a surface modification solvent and silicon powder, stirring, and drying to obtain surface-modified silicon powder; S2, adding the surface-modified silicon powder, water-soluble carbon source, soluble inorganic salt and carboxylated carbon nanomaterial into the acidic aqueous solution and mixing them uniformly; S3, the mixed solution is passed through a spray dryer to prepare micron-sized silicon-carbon secondary particles, which are then sintered at high temperature in a vacuum furnace under the protection of an inert gas and cooled to room temperature; S4: After high-temperature sintering, the product is washed to remove soluble inorganic salts and then dried at low temperature under vacuum to obtain the final product.
[0024] In step S1, the modifier is selected from one of organosiloxane, polyether-modified hydrophilic water-soluble silicone oil, and PVP hydrophilic solvent. The modifier mainly changes the hydrophilic properties of the silicon surface to increase its hydrophilicity.
[0025] The surface modification solvent is selected from one of silane coupling agent, titanate, and stearic acid; the silane coupling agent includes but is not limited to one of amino, epoxy, and vinyl.
[0026] In step S1, the silicon powder is selected from crystalline silicon particles of arbitrary shape, with a size of 100-500 nm, and a dimension of the particles in one direction is less than 200 nm; the mass ratio of the modifier to the silicon powder is 2.5-8:16, so that the thickness of the molecular layer covering the surface of the silicon particles is 3-20 nm.
[0027] In step S2, the water-soluble carbon source is an aqueous solution of a polar polymer, including but not limited to an aqueous polyurethane resin solution, a water-soluble polyethylene glycol solution, and a methyl cellulose solution; the carboxylated carbon nanomaterial is one or more of carboxylated carbon nanotubes, carboxylated graphene, and carboxylated carbon nanofibers; and the radial dimensions of the carboxylated carbon nanomaterial in different directions are less than 300 nm.
[0028] In step S2, the soluble inorganic salt is selected from one or more inorganic salts that can crystallize at 80-100°C and are soluble in water, including but not limited to one or more inorganic salts such as potassium salts, sodium salts, ammonium salts, nitrates, and acetates that can crystallize at 100°C and are soluble in water. Specifically, potassium chloride, calcium chloride, sodium sulfate, etc. can be used. During high-temperature sintering, the crystals mix with the silicon particles to form secondary particles coated with carbon. Finally, the inorganic salt is dissolved and removed.
[0029] In step S2, the acidic aqueous solution includes at least one of weakly acidic acetic acid solution, citric acid solution, acetic acid solution, and carbonic acid, and the pH value is 3-5.
[0030] In step S2, the mass ratio of silicon to carbon element in the water-soluble carbon source is 1:1-3, the mass ratio of the soluble inorganic salt to silicon is 1:1-1.5, and the mass ratio of silicon to carboxylated carbon nanomaterial is 1:0.1-0.5.
[0031] In step S3, the inert gas is selected from nitrogen and argon, the sintering temperature is 800-900° C., and the holding time is 0.5-1.5 hours.
[0032] During S3, a suspension containing silicon powder, a water-soluble carbon source, a soluble inorganic salt, and carboxylated carbon nanomaterials is pumped into a nozzle and transported by air pressure into a high-temperature drying chamber. The droplets enter the drying chamber. As the water on the surface of the microspheres evaporates, the inorganic salts precipitate on the surface of the microspheres, and together with the water-soluble carbon source, they prevent the internal vapor from escaping. Next, the vapor pressure inside the microspheres gradually increases. The heat from the evaporation of water changes the temperature gradient on the surface of the droplets. Under the action of inertia, the droplet surface deforms and forms a partial surface depression 1-1. The particles collapse from their spherical shape to form a cross-linked body of silicon debris 1-2 and carbon nanomaterial 1-3 with continuous, arc-shaped boundaries. When the particles are formed, the water-soluble carbon source coats the surface of the silicon and carbon nanomaterials.
[0033] When the concave porous silicon-carbon particles of the present invention are prepared into a negative electrode for a lithium-ion battery, the silicon-carbon composite material is mixed with carbon black (SP) microspheres as an active material for lithium storage and then coated into a film layer, in which SP acts as a conductive medium.
[0034] When silicon-carbon particles have a concave surface, the tap density of the negative electrode is high, the gaps are small, the SP is tightly packed, and the gaps between silicon-carbon particles are small. Therefore, the contact area between the particles in the prepared negative electrode is large and the conductive paths are abundant. When lithium ions enter the silicon-carbon material, the lithium-silicon alloy particles expand, and the concave surface under the particles provides space for expansion.
[0035] The nano-carbon material in the composite particles of the present invention has an ordered structure, which improves the internal conductivity and ion transport capabilities of the silicon-carbon particles. At the same time, it can also serve as a buffer structure to absorb silicon expansion stress, avoid cracking of the silicon-carbon particles, and also avoid cracking and falling off of the negative electrode. Example 1
[0036] This embodiment is a method for preparing recessed porous silicon-carbon particles with added carbon nanotubes, comprising the following steps: S1: Mix and stir the modifier aminosilane coupling agent with silicon powder. The mass ratio of the modifier to the Si powder is 1:4, so that the surface coverage of the silicon particles is about 10nm. After drying, the surface-modified silicon powder is obtained.
[0037] S2, adding the modified silicon powder, aqueous polyurethane solution, soluble potassium chloride and carboxylated carbon nanotubes into an acetic acid aqueous solution and mixing them evenly, and stirring the raw materials for 48 hours to form a uniform colloidal solution.
[0038] S3: The colloidal solution was spray dried to prepare micron-sized silicon carbon particles. The SEM morphology of the particles is as follows: Figure 1 By controlling the spray drying parameters such as air pressure, airflow, and peristaltic pump speed, and utilizing the matching degree between the viscosity and fluidity of the colloidal solution and the above parameters, silicon-carbon composite particles (SCT) with a particle size of 0.5-8 μm were prepared. The sample without carbon nanotubes was designated SC.
[0039] This embodiment uses potassium chloride concentration to change the surface tension and viscosity of the droplets, and changes the cross-linking force of carboxylated carbon nanotubes on the surface of modified silicon particles by the solid content and polymerization amount of polyurethane. Specifically, the spray dryer pumps a suspension containing silicon powder, water-soluble carbon source, soluble inorganic salt, and carboxylated carbon nanotubes into the nozzle, and transports it into the high-temperature drying chamber through air pressure. The droplets enter the drying chamber. As the water on the surface of the microspheres evaporates, the inorganic salts precipitate on the surface of the microspheres, and together with the water-soluble carbon source, they hinder the overflow of internal steam. Then, the vapor pressure inside the microspheres gradually increases, and the heat of water evaporation changes the temperature gradient on the surface of the droplets. Under the action of inertia, the surface of the droplets deforms and forms a partial surface depression 1-1. The particles collapse from the spherical shape to form a cross-linked body of silicon debris 1-2 and carbon nanotubes 1-3 with continuous and arc-shaped boundaries. When the particles are formed, the water-soluble carbon source is coated on the surface of the silicon and carbon nanotubes.
[0040] Under the action of the vortex airflow, micron-sized silicon-carbon composite particles are screened out and sintered at high temperature to further carbonize the water-soluble carbon. Inert gases such as nitrogen are used as protective gases during the sintering process to remove H and O components while avoiding oxidation of the carbon coating layer and the surface of the silicon particles. The carbon layer on the surface of the silicon particles undergoes a carbonization reaction during high-temperature sintering, forming a short-range ordered and long-range disordered carbon composite layer.
[0041] S4: The product after high-temperature sintering is washed with a solvent that can dissolve inorganic salts and does not react with silicon and carbon to remove the soluble inorganic salts, and then dried to obtain the recessed porous silicon-carbon particles with added carbon nanotubes.
[0042] Specifically, the solvent can be acetic acid, ethanol, water or other reagents that can dissolve potassium chloride and do not react with silicon and carbon. After washing, the concave structure of the particles does not collapse qualitatively, and more pores are formed inside. The pores of the particles are shown in the attached figure. Figure 2 As shown in the figure, the pore capacity of the particles with added carbon nanotubes is larger than that of the particles without added carbon nanotubes.
[0043] The acidic aqueous solution in step S1 of this embodiment includes at least one of an acetic acid solution and a citric acid solution, and has a pH of 3-5. Specifically, the acidic aqueous solution facilitates the binding of the water-soluble carbon source to the surfaces of the modified silicon particles and the carbon nanotubes. Furthermore, in step S1, the mass ratio of silicon to carbon in the water-soluble carbon source is 1:2, the mass ratio of the soluble inorganic salt to silicon is 1:, and the mass ratio of silicon to carbon nanotubes is 1:0.3.
[0044] Specifically, when the mass of carbon is greater than that of silicon, carbon forms a wrapping effect on silicon particles in the form of amorphous carbon and amorphous carbon structural layers, and surface depression can be controlled by controlling the amount of soluble KCl and carbon nanotubes.
[0045] Furthermore, in step S3 of this embodiment, the air flow outlet temperature during the spray dryer granulation process is 90°C and the gas pressure is 22.4 kg / cm 2 During the high-temperature sintering in step S3, nitrogen protection was added. The temperature was raised to 850°C, held for 1.5 hours, and then naturally cooled to room temperature. The recessed porous silicon-carbon particles containing carbon nanotubes obtained by the above method had a size of approximately 3 to 8 μm.
[0046] After the silicon-carbon particles with added carbon nanotubes are formed into a film to prepare the negative electrode of the lithium battery and cycled, the particle structure of the particles with added carbon nanotubes is intact after the cycle, unlike the particles without added silicon-carbon particles. The changes of the particles during the cycle are as follows: Figure 4 As shown in the figure, the silicon-carbon particles with added carbon nanotubes maintain a complete particle structure after cyclic charge and discharge at the negative electrode, which is beneficial to the cycle life of the battery. Example 2
[0047] In this example, 2.0 g of modified silicon powder, 2.0 g of polyethylene glycol PEG6000, 1.35 g of CaCl2, and 0.15 g of carboxylated graphene were added to deionized water. After stirring the mixture for 24 hours, micron-sized silicon-carbon particles were prepared by spray drying. During the granulation process, the air inlet temperature was 140°C, the air outlet temperature was 95°C, and the gas pressure was 33 kg / cm 2 .
[0048] The silicon-carbon particles were heated to 900°C under nitrogen, held for 1 hour, and then naturally cooled to room temperature. The sintered product was washed three times with acetic acid to remove CaCl2, then washed with ethanol, and dried.
[0049] The surface morphology of the prepared concave porous silicon carbon particles SCG with added carbon nanotubes is as follows Figure 3 shown.
[0050] The mechanism of formation of the non-spherical particles prepared by the present invention is as follows Figure 5 As shown, carbon nanotubes (CNTs) can be replaced by graphite or carbon nanofibers. Adding the silicon-carbon particles prepared by the above method to the negative electrode material of a lithium battery can effectively increase the specific capacity of the negative electrode, while also improving the stability of the negative electrode and extending the cycle life of the negative electrode material.
Claims
1. A concave porous silicon-carbon particle with high ionic conductivity, characterized in that: The concave porous silicon-carbon particles are provided with partial surface depressions (1-1) on their surfaces, forming a cross-linked body of silicon debris (1-2) and carbon nanomaterials (1-3) with continuous and arc-shaped boundaries.
2. A method for preparing concave porous silicon-carbon particles with high ionic conductivity, characterized in that: The steps include: S1, mixing a modifier, a surface modification solvent and silicon powder, stirring and drying to obtain surface-modified silicon powder; S2, adding the surface-modified silicon powder, the water-soluble carbon source, the soluble inorganic salt and the carboxylated carbon nanomaterial into the acidic aqueous solution and mixing them evenly; S3, the mixed solution is spray dried to prepare micron-sized silicon-carbon secondary particles, and the silicon-carbon secondary particles are sintered at high temperature in a vacuum furnace under the protection of inert gas and cooled to room temperature; S4: After high-temperature sintering, the product is washed to remove soluble inorganic salts, and low-temperature dried under vacuum to obtain the final product.
3. The method for preparing a concave porous silicon-carbon particle with high ionic conductivity according to claim 2, characterized in that: In the step S1, the modifier is selected from one of organic siloxane, polyether-modified hydrophilic water-soluble silicone oil, and PVP hydrophilic solvent.
4. The method for preparing concave porous silicon-carbon particles with high ion conductivity according to claim 2, characterized in that: The surface modification solvent is selected from one of silane coupling agent, titanate, and stearic acid; the silane coupling agent includes but is not limited to one of amino, epoxy, and vinyl.
5. The method for preparing concave porous silicon-carbon particles with high ion conductivity according to claim 2, characterized in that: In the step S1, the silicon powder is selected from crystalline silicon particles of arbitrary shape, with a size of 100-500nm, and the dimension of the particles in a certain direction is less than 200nm; the mass ratio of the modifier to the silicon powder is 2.5~8:16, so that the thickness of the molecular layer covering the surface of the silicon particles is 3-20nm.
6. The method for preparing concave porous silicon-carbon particles with high ion conductivity according to claim 2, characterized in that: In the step S2, the water-soluble carbon source is selected from a polar polymer aqueous solution, including but not limited to an aqueous polyurethane resin solution, a water-soluble polyethylene glycol solution, and a methyl cellulose solution; the carboxylated carbon nanomaterial is selected from one or more of carboxylated carbon nanotubes, carboxylated graphene, and carboxylated carbon nanofibers; and the radial dimensions of the carboxylated carbon nanomaterial in different directions are less than 300 nm.
7. The method for preparing concave porous silicon-carbon particles with high ion conductivity according to claim 2, characterized in that: In step S2, the soluble inorganic salt is selected from one or more inorganic salts that can crystallize at 80-100°C and dissolve in water, including but not limited to one or more inorganic salts such as potassium salts, sodium salts, ammonium salts, nitrates, acetates, etc. that can crystallize at 100°C and dissolve in water.
8. The method for preparing concave porous silicon-carbon particles with high ion conductivity according to claim 2, characterized in that: In step S2, the acidic aqueous solution includes at least one of weakly acidic acetic acid solution, citric acid solution, acetic acid solution, and carbonic acid, and the pH value is 3-5.
9. The method for preparing concave porous silicon-carbon particles with high ion conductivity according to claim 2, characterized in that: In the step S2, the mass ratio of silicon to carbon element in the water-soluble carbon source is 1:1 to 3, the mass ratio of the soluble inorganic salt to silicon is 1:1 to 1.5, and the mass ratio of silicon to the carboxylated carbon nanomaterial is 1:0.1 to 0.
5.
10. The method for preparing concave porous silicon-carbon particles with high ion conductivity according to claim 2, characterized in that: In the step S3, the inert gas is selected from nitrogen and argon, the sintering temperature is 800-900° C., and the holding time is 0.5-1.5 hours.
Citation Information
Patent Citations
Preparation method of silicon / carbon multi-component composite negative electrode material
CN103545493A
Nanometer silicon particle-graphite flake-carbon nanotube composite material and preparation method and application thereof
CN105226253A
Porous carbon nano-tube flexible battery material containing nano-silicon and preparation method thereof
CN109524648A
Silicon-based negative electrode material, and preparation method and application thereof
CN112952059A
Porous silicon / carbon composite negative electrode material of lithium ion battery, preparation method of porous silicon / carbon composite negative electrode material and lithium ion battery
CN114695887A